SANITARY PROTECTION OF THE TERRITORY OF THE RUSSIAN FEDERATION. REPORT 1. THE PRINCIPLES OF DIFFERENTIATED APPROACH TO THE ORGANIZATION OF ACTIVITIES OF THE SANITARY PROTECTION OF THE TERRITORY AT THE LEVEL OF MUNICIPALITIES - V. A. Vishnyakov; A. K. Noskov (Acta Biomedica Scientifica, 2012)
A differentiated approach to the organization of measures for sanitary protection of the territory, based on the analysis of the transport and. facility components of risk emergency situations in the field of sanitary-epidemiological welfare of the population is proposed. The total evaluation of the external and. internal components of the risk emergency situations for each municipality of a region of the Russian Federation allows to determine type of readiness to conduct activities of the sanitary protection of the territory for a given area. The ranking of the region of the Russian Federation will contribute to the achievement of optimum readiness of the Institutions of Public Health and. sanitary-epidemiological surveillance at the level of municipalities to the occurrence of diseases, requiring measures of sanitary protection.